Broadway Street, Bridgetown Barbados, British West Indies. 30248 - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
This photo portrays Broadway [Broad Street] Street in Bridgetown, Barbados British West Indies. The busy street scene shows various modes of transports including cars and bicycles. Many people are in the streets goinga bout their activities. Info. At the back: O.N.T.B STAMP: 1/2 Pence Barbados Postage Stamp STAMP: 1 1/2 Pence Barbados Postage stamp STAMP: 1 Barbados Post Office stamp Photogelatine Engraving Co. Limited. Ottawa STAMP: “P E CO OTTAWA” Indecipherable hand written note
Broad Street, Bridgetown Barbados, British West Indies. 30248
Landscape, colour, 4 x 6 in., divided back
Keywords: Cars; Bicycles; Buildings; People; Vehicles; Transportation; Cityscapes